Body Mass Index Modified Predictive Ability Of Biomarkers For Protein-Energy Wasting In Prevalent Hemodialysis Patients - Hirokazu Honda; Kanji Shishido; Tetsuo Michihata; Hiroaki Ogata; Fumihiko Koiwa; Eriko Kinugasa; Tadao Akizawa (The Korean Society of Nephrology, 2012)
Protein-energy wasting (PEW) is crucial complication in prevalent hemodialysis (HD) patients. Abnormality of biomarkers such as IL-6, NT-pro-BNP, and adiponectin (ADPN) contribute to PEW. However, associations of the biomarkers with PEW according to BMI levels have not been fully evaluated. Thus those associations were assessed by a cross-sectional cohort study of prevalent HD patients (n=386). PEW was defined by subjective global assessment (n=108). IL-6 levels were inversely, and NT-pro-BNP and ADPN levels were positively correlated with BMI levels. Odds ratio (OR) of log IL-6 (OR 1.5, CI 1.0, 2.2), log NT-pro-BNP (OR 1.7, CI 1.3, 2.2), and log ADPN (OR 1.9, CI 1.1, 3.2) to PEW were significantly increased in logistic multivariate regression model. ORs of log NT-pro-BNP and log ADPN for PEW were progressively increased in patients with threshold 21 kg/m2<BMI, but progressively decreased in those below this threshold. On the other hand, OR of log IL-6 for PEW was progressively decreased in patients with threshold 21 kg/m2<BMI, but similar in those below this threshold. These associations were confirmed by the models adjusted with confounder. In conclusions, predictive values of IL-6, NT-pro-BNP and ADPN for PEW state may be dependent on BMI levels in prevalent HD patients.fx1